A laboratory test method to realistically simulate air side fouling of condensers (RP-1705). (2nd July 2020) - Mehrabi, Mehdi; Yuill, David
Abstract : This paper describes the development of a method that can be used to simulate in a laboratory the effects of air side fouling of condensers from split system air conditioners. The method includes a synthetic fouling agent that realistically mimics field fouling. The fouling agent was developed by considering the fouling materials and effects on heat transfer and air side pressure drop that were measured on a set of condenser coils that had been fouled in situ. The proposed fouling agent matches these effects by combining a fiber component with a particulate component. The particulate component is made from quartz dust that has a particle size distribution based on averages of size distributions in samples collected from condensers in Omaha, NE and Las Vegas, NV. The fouling agent is applied to coils with several different designs, including a range of fin pitches, and plate fin, spine fin, and microchannel configurations. The rates of fouling deposition, as well as the effects of fouling on coil performance, are shown and compared for these coils.